RAW MATERIAL HANDLING FOR IMPROVEMENT QUALITY OF FOOD PRODUCT - Ika Gusriani; Bosman Sidebang (CV. Multi Kreasi Media, 2022)
The Women's Group who cares for the Environment and the Women's Community who Save the World Heritage Site in Curup Rejang Lebong, Bengkulu are facing challenges related to post-harvest handling of agricultural products, especially jackfruit, kecombrang, avocado, durian and several other forest products. In overcoming these problems, community service is carried out with the aim of educating partners regarding post-harvest handling of products to avoid damage if they are not properly cared for. Food spoilage can be caused, among others: growth and activity of microorganisms, especially bacteria, molds and yeasts, activity of enzymes in foodstuffs, insects, parasites and rats, temperature including heating and cooling, water content, presence of air including oxygen, light and too long and other factors. Anticipation of damage can be done by post-harvest management of food product raw materials, including Sorting, Sizing, Grading, Aging/curing, Degreening, Precooling, Coating, Packing. The expected result of this service is the understanding of partners about post-harvest handling and the stages of post-harvest treatment of agricultural products. Keywords: Grading, Post-harvest, Service, Sorting.